Polymer nanocomposite membranes for pesticides removal - Khairul Anwar, Mohamad Said; Ibrahim, Yakub; Mohamed Afizal, Mohamed Amin; Md. Rezaur, Rahman; Muhammad Khusairy, Bakri (Woodhead Publishing is an imprint of Elsevier, 2025)
Pesticides are compounds, the definitions of which vary from nation to nation and change over time. They are made to be poisonous to some species but harmless to nontargeted organisms and ecosystems. Certain chemicals or mixtures, such as insecticides, herbicides, fungicides, and pest-control agents, are used to prevent pests. Although they might be helpful in certain situations, pesticides can harm both humans and the environment. Pesticides are persistent and have a lengthy half-life in the environment. pesticides have been removed from water and wastewater using a range of physical, chemical, and biological methods. Adsorption, biosorption, reverse osmosis, ozonation, photocatalysis, membrane technology, and advanced oxidation process are all included in the discussed techniques.